The Effect of Green Economy Incentive on MSMEs in Implementing Circular Economy Practice as Part of Sustainability Economy - Mawardi, Hakimah; Wibowo, Mas Wahyu (International Journal of Management and Digital Business, 2025)
This study examines the implementation of circular economy practices in Micro, Small, and Medium Enterprises (MSMEs) in the Jakarta area, considering the mediating roles of variables such as Environmental Commitment and green ambidexterity innovation. The research was conducted in 10 MSME centers operating in Jakarta, with a total population of 164 MSME actors. Data collection was carried out through a quantitative survey using a questionnaire designed with a Likert scale of 1-5. The results indicate that Green Economy Incentive (GEI) has a positive and significant effect on Circular Economy Practice (CEP) with an influence value of 0.625. GEI also enhances Green Ambidexterity Innovation (GAI), which significantly mediates the relationship between GEI and CEP. However, Environmental Commitment (EC) does not mediate the relationship between GEI and CEP. These findings suggest that green economy incentives strengthen the implementation of circular economy practices by increasing environmental awareness and the adaptive innovation capabilities of MSMEs, thus playing a crucial role in accelerating the adoption of sustainable practices and the transformation towards a green economy in the MSME sector in Jakarta.